The Influence of Perception on Community Acceptance of Sharia Pawnbroking in Padang City - Reza Fahmi; Prima Aswirna; Meirison; Putri Nadya Salsabila (Journal of Islamic Economics Studies and Practices, 2025)
This study aimed to analyze the influence of public perception on the acceptance of Sharia Pawnbroking (Gadai Syariah) services in Padang City, Indonesia. Utilizing a quantitative research design, the study employed a survey method on a sample of 128 respondents selected through purposive sampling. Data analysis involved descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, and simple linear regression. The results indicated that while the majority of the community held a positive perception (70.31%) towards Sharia Pawnbroking, the actual level of service acceptance remained low, with 60.94% categorized as low acceptance. However, a strong, positive, and significant relationship was found between perception and acceptance (r ≈ 0.55–0.65; p < 0.05) , with perception significantly influencing acceptance (sig < 0.05). The finding suggests that positive perceptions, driven by religious alignment, are crucial, yet they are not sufficient to overcome practical barriers such as low financial literacy, limited access, high administrative costs, and persistent social stigma. Therefore, successful implementation requires an integrated strategy of intensive public education and substantial improvement in service accessibility and transparency.